PENINGKATAN PEMAHAMAN KONSEP PENGURANGAN BILANGAN MELALUI MEDIA PERMAINAN TRADISIONAL GAPUK - Yeni Lativah; M. Rifqi Rijal; Wida Rachmiati (Universitas Islam Malang, 2023)
This study aims to improve students understanding of the concept of subtraction.This research is motivated by students difficulties in understanding the concept of arithmetic subtraction operations, this can be seen from the results of observations made by researchers, namely the learning process carried out has not been equipped with the use of appropriate learning media and a passive learning atmosphere, causing students understanding of the concept of reduction to be low. Therefore, thr researchers used the traditional game media gapuk in subtractin material as a solution to these problems in the hope that students understanding of concept of substraction can increase.The research method used in this research is classroom action research (PTK). This PTK is carried out in two cycles consisting of planning, implementing actions, observing and reflecting. The data analysis technique used is the class average test and the percentage of completeness. The results of this study indicate that by using the traditional game media, gapuk can improve the understanding of the concept of subtraction for class II students at SDN Curug Barang Serang, Serang Regency. This can be seen from the increase in student mastery in the first cycle 55,56 % and average value of 70,00, then increased in the second cycle, students who completed reached 83,33% and the average score was 75,56. Based on the results of the study, it can be concluded that the use of traditional gapuk game media can improve the understanding of the concept of subtraction for class II students at SDN Curug Barang Serang Regency.